Dažādu urbšanas metožu pielietošana grunts paraugu noņemšanā un slāņu robežu noteikšanā - Niedrājs, Juris (Latvijas Universitāte, 2008)
Maģistra darbā dots īss ieskats urbšanas darbu vēsturē, to pielietošanā inženierizpētes un ģeotehnikas jautājumu risināšanā, apskatīti dažādi urbšanas veidi, to pielietojums dažādu grunšu urbšanā un atšķirīgu izpētes mērķu realizēšanā. Īsi apskatīti Latvijas Republikas normatīvie akti un likumi, kuri reglamentē ģeotehnisko darbu izpētes veikšanu. Dots ieskats par metodēm, ar kādām notiek saistītie laboratoriskie, kamerālie un lauka pētījumi. Darba gaitā savākts materiāls par paša, gan citu pētnieku apsekotām dažādas ģenēzes un morfoloģijas mālainām gruntīm. Apsekota atšķirība to metodikā un rezultātos. Pēc apkopoto materiālu analīzes ir apskatīta iespēja pielietot aprēķinus no urbumiem iegūtu traucētu grunšu paraugu fizikālo īpašību noteikšanai, kas atvieglos urbšanas datu izmantošanu iežu un grunšu pētījumos. Atslēgas vārdi: urbšana; grunts; slānis

The necessity of drilling in Latvia has increased due to many reasons – increase in construction, reconstruction and renovation of buildings, and among other aspects, drinking water systems as well. Therefore the demand for expert engineering investigations are growing rapidly, as further existence of the object depends on them. They are required by either the construction of the object or by Latvian laws and regulations. Drilling as a historical practice dates back 2000 years and is still a significant issue. The goal of this study is by employing different drilling techniques to evaluate soil samples in uniform soil strata and to find the most suitable method. The tasks of this study are to analyze available theoretical literature in the fields of engineering geology, drilling methods, to describe any applied methods and proceed with field studies. During the process of writing this study, considerable amount of information concerning clayey soil of different genesis and morphology has been gathered, different methods and results have been inspected. After the materials have been gathered and analyzed, a possibility of performing calculations on soil samples from disordered soil for physical properties has been proposed. This shall prove to be helpful in facilitating the usage of drilling data on rock and soil exploration. An insight on methods about coherent laboratorial, cameral and field studies has been given. It is important to use the most appropriate method for taking soil samples and determining the boundaries of the strata. Keyword: drilling, grow, sheet
Use of various drilling methods for soil sampling and bed boundary determination
Keywords: Ģeoloģija